Mapping the world of coaching science: A citation network analysis - Rangeon, S.; Gilbert, W.; Bruner, M. W. (Journal of Coaching Education, 2012)
The purpose of the present study was to use citation network analysis to identify key publications and influential researchers in coaching science. A citation network analysis was conducted on references of English-language peer-reviewed coaching research articles published in 2007 and 2008 (n=141 articles; 3,891 references). Publications were coded for type (e.g., conceptual, empirical) and topic (e.g., efficacy, coach development). The structure of the field was revealed through the creation of a co-authorship network. Results show that coaching science is highly influenced by a small set of key publications and researchers. The results provide a unique overview of the field and influential authors, and complement recent overviews of coaching science (Gilbert & Trudel, 2004; Lyle & Cushion, 2010; McCullick et al., 2009).